THE CONCEPT OF CLASSROOM USAGE AS A MEDIA LEARNING OF ISLAMIC RELIGION IMPROVING STUDENT LEARNING MOTIVATIN IN PANDEMIC - Diva Sri Wahyuni Ahmad (Proceeding International Seminar of Islamic Studies, 2022)
Teaching activities are less effective when they are not accompanied by media to support the process. Because the learning medium is a tool for delivering materials to students and making it easier in the learning process. Frequently in the online learning process there is saturation for students in listening to material presented by teachers, it results in grades that become less effective in the teaching activities. To overcome this is to prevent that from happening, one must take note of the creativity of an educator. Through the medium of learning the learning process will stimulate the students' morale. Without the material learning media to be presented is less explicit to students. One of the most effective mediums in classroom learning is the classroom. Classroom media are wet-based platches-designed to facilitate educators and student learning activities. Classroom applications are also free-use mixed-online learning applications. Classroom media also has an advantage and advantage compared with other learning media, which is a quick and comfortable classroom setting, efficient and time efficient, capable of increasing cooperation and communication, centralized data storage, efficient, and speedy sharing of resources. With classroom media there is room for all the material that teachers bring it.Keywords:The concept, learning, classroom